Ellagic acid attenuates muscle atrophy in STZ-induced diabetic mice - Liu, X; Cheng, C; Deng, B; Liu, M (Physiological research, 2022)
Diabetes is closely connected with skeletal muscle dysfunction. Ellagic acid (EA) possesses a variety of bio-effects and is applied to the improvement of diabetes. The purpose of this study was to explore the potential improvement effect and mechanisms of EA in streptozotocin (STZ)-induced diabetic muscle atrophy. The model of diabetic mice was established by intra-peritoneal STZ to evaluate treatment effect of EA (100 mg/kg/d for 8 weeks) on muscle atrophy. Our data exhibited that EA enhanced fiber size and weight of gastrocnemius, and promoted grip strength to relieve STZ-induced muscle lesions. In serum, the levels of Creatine kinase (CK), lactate dehydrogenase (LDH), total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL) were inhibited, while high-density lipoprotein cholesterol (HDL) level was enhanced by EA treatment in diabetic mice. In gastrocnemius, EA decreased Atrogin-1 and MuRF-1 expressions to relieve STZ-induced muscle atrophy. Moreover, EA increased NRF-1 and PGC-1alpha expressions to alleviate mitochondrial disorder. Meanwhile, EA suppressed CHOP and GRP-87 levels to relieve ER stress. Lastly, EA inhibited BAX expressions and enhanced Bcl-2 expressions to mitigate apoptosis. In conclusion, EA is preventing the event of STZ-induced gastrocnemia by amelioration of mitochondrial dysfunction, ER stress and apoptosis, and could be used in the protection and therapeutic of muscle atrophy in diabetes.
Keywords: experimentální diabetes mellitus; svalová atrofie; myši; Muscular Atrophy; kyselina ellagová; zvířata; Mice; streptozocin; Diabetes Mellitus, Experimental; Muscle, Skeletal; kosterní svaly; Cholesterol; Ellagic Acid; Streptozocin; cholesterol; Animals